DIPLOMASI PUBLIK INDONESIA DALAM MENJADIKAN KALDERA TOBA SEBAGAI UNESCO GLOBAL GEOPARK - Laposa Mirta Dea Roja; Umi Oktyari Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The super volcanic eruption of the Toba Volcano 74,000 years ago had a significant impact on the world. The enormity of the eruption, made the geographical conditions of the Toba Volcano area turn into a large caldera and currently known as the Toba Caldera. Toba Caldera has a unique geological, biological and cultural diversity so that this area has the potential to become a tourism area. The Indonesian government has made the Toba Caldera as one of the Super Priority Tourism Destinations (DPSP) so that the Geopark concept is the most strategic choice to preserve and utilize the Toba Caldera area. The Geopark concept put forward is triggered by the UNESCO Global Geopark (UGGp) program which is able to bring Geopark areas to countries in the world to experience a rapid increase in the number of tourist visits. Recognizing this phenomenon, the Indonesian government uses public diplomacy as an effort to obtain global Geopark certification from UNESCO. This study uses qualitative research methods with data collection techniques sourced from interviews, several books, journals, research documents, articles, internet pages and other relevant sources. This study also uses the perspective of Neoliberalism with the theory of Diplomacy which puts forward the concept of Public Diplomacy. The results of this study indicate that Indonesian public diplomacy through news management, strategic communication, and relationship building has an important role in making the Toba Caldera a UNESCO Global Geopark. Through public diplomacy, the government is able to fulfill the substantial prerequisites from UNESCO, namely community empowerment in preserving geological heritage and utilizing it in the tourism sector. In addition, Indonesia is also able to communicate the new image of the Toba Caldera as 5 Super Caldera Toba Geoparks (Supervolcano, Super Big Volcanic Lake, Super Beautiful Landscape, Super Unique Cultural Heritage, and Super Unique Biodiversity) to the world community. Keywords: Geopark, Public Diplomacy, Toba Caldera, UNESCO